Harnessing strontium in regenerative dentistry: progress and perspectives - Zhang, Wenjing; Wei, Lingfei (Frontiers in Bioengineering and Biotechnology, 2025)
Strontium (Sr), an alkaline earth element characterized by its unique bioactivity, has garnered significant interest in the field of oral regenerative medicine. This interest is primarily due to its inherent presence in bone tissues, particularly in growth plates and trabeculae, and its ability to influence bone metabolism through the calcium-sensing receptor (CaSR). Various signaling pathways, including MAPK/ERK1/2 and Wnt/NFATc, are involved in the mechanisms behind these effects. Strontium-doped biomaterials progressively release Sr2+ ions, which impart a variety of biological effects, among these are the stimulation of osteoblast proliferation and differentiation, and the exhibition of antibacterial and anti-inflammatory characteristics. Moreover, these ions are involved in regulating the deposition of the extracellular matrix. Collectively, these characteristics underscore the potential utility of strontium-doped biomaterials for the regeneration of soft and hard tissues, exemplified by applications in alveolar bone reconstruction and the osseointegration of dental implants. Despite these advantages, numerous challenges persist, particularly in relation to degradation kinetics, long-term in vivo stability, and translational applications. This review offers a comprehensive examination of the biological roles of strontium, recent advancements in its integration into biomaterials, and the underlying molecular mechanisms. Additionally, it addresses current limitations and proposes potential strategies for optimization, thus offering a theoretical basis for the future creation of novel oral regenerative materials.